Investigação matemática : tratamento da informação no ensino fundamental - Balke, Marlova Elizabete (2011)
This research, involving students from 8th grade of elementary school basic education at a school in state schools in the city of Hinton, north of Rio Grande do Sul, aimed to analyze the potential of the methodology of mathematical research in the development block content information processing. Some studies (Lopes, 1998; Buehring, 2006) indicate that this content is rarely worked in school, but necessary and important for basic education and to people's lives, just as the National Curriculum Parameters highlight its importance in school curriculum. The research methodology is a qualitative approach, which was collected methodological tools of math classes developed by the researcher in her role as teacher. The question guiding the research is presented as: To what extent the methodology of mathematical research enhances the appropriation of meaning of concepts that characterize the content block information processing? The theoretical basis for the research consists of authors such as Bridge, Vygotsky, Duval, among others, which highlight important aspects for consideration in the classroom. It was found that the development of mathematical research activities allowed in the classroom interactions, which contributed to and worsened the appropriation of the concepts of information processing, in with the student effected their learning with interest and the researcher can reflect on their practice for a change of attitude in the management of classes. We conclude that it is necessary that an educational context and, through interactions in the environment of the classroom, learning takes place, as well as that for mathematics education, the research methodology leverages the appropriation of mathematical meanings of the concepts of field information processing, and other content